Optimization of click chemistry of ferrocene derivatives on acetylene-functionalized silicon(100) surfaces - Ciampi, Simone; Le Saux, G.; Harper, J.; Gooding, J. (Wiley - VCH Verlag GmbH & Co. KGaA, 2008)
The optimization of the reaction conditions for copper-catalyzed azide-alkyne ,click- cyclo-addition reactions used to covalently confine substituted ferrocene derivatives on passivated silicon(100) surfaces is reported. Variations in the observed reaction yields and the extent of surface contamination as a function of the source of the copper catalyst and the solvent system used in the ,click- procedure were evaluated spectroscopically. The electronic communication between the ferrocene centre and the underlying semiconductor surface was investigated by means of cyclic voltammetry and found to be consistent with that expected for a well-behaved and robust redox interface. © 2008 Wiley-VCH Verlag GmbH&Co. KGaA.